Quaternary electrocatalytic anode material and preparation method and application thereof

By loading molybdenum, iron, and transition metals onto nickel foam to form a composite oxide, the activity and stability issues of electrocatalytic anode materials in OER and MOR are solved, achieving efficient and stable electrolysis performance suitable for commercial electrolytic cell applications.

CN119121274BActive Publication Date: 2025-11-28ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411256956.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-11-28
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

Existing electrocatalytic anode materials suffer from problems such as insufficient active sites, poor conductivity, and low stability in oxygen evolution reaction (OER) and methanol oxidation reaction (MOR), making it difficult to meet the industrial requirements of high efficiency, stability, and low cost.

Method used

Using nickel foam as a carrier, molybdenum, iron, and another transition metal element (such as vanadium, tungsten, manganese, or cobalt) are loaded to form a composite oxide. Stable multi-metal oxides are formed by high-temperature calcination, which optimizes the electronic structure and enhances the covalent nature of the metal-oxygen bond.

Benefits of technology

It significantly reduces the overpotential of OER and MOR reactions, improves the stability and catalytic activity of the material, and is suitable for large-scale electrolysis applications in commercial electrolyzers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121274B_ABST
    Figure CN119121274B_ABST
Patent Text Reader

Abstract

The application relates to the field of electrochemistry, and discloses a quaternary electrocatalytic anode material and a preparation method and application thereof. The quaternary electrocatalytic anode material takes a nickel foam as a carrier, a molybdenum element, an iron element and another secondary group metal element are deposited on the surface layer of the nickel foam, and the surface layer is a composite oxide of iron, nickel, molybdenum and another secondary group metal. The obtained quaternary electrocatalytic anode material can significantly improve the performance of electrocatalytic water splitting and oxygen evolution and electrocatalytic methanol oxidation, and has great application potential in large-scale commercial electrolytic cells.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of electrochemistry, in particular to a quaternary electrocatalytic anode material and a preparation method and application thereof. BACKGROUND

[0002] Today, renewable energy conversion and storage technology is becoming a research hotspot, and electrochemical catalysis as a bridge connecting the conversion of electrical energy and chemical energy, its performance optimization is directly related to the improvement of energy utilization efficiency. Especially in the oxygen evolution reaction (OER) and methanol oxidation reaction (MOR), high-efficiency and stable electrocatalytic anode material is the key factor restricting the breakthrough of technology.

[0003] OER reaction involves multi-step electron and proton transfer, the process is complex and the kinetics is slow, often requires a higher overpotential to drive, which greatly limits the energy conversion efficiency. And the incomplete oxidation of methanol in MOR reaction is easy to cause catalyst poisoning, reduce the catalytic activity and stability. Traditional electrocatalytic anode material is not up to the challenge. There are problems such as lack of active sites, poor conductivity, and poor stability, which is difficult to meet the needs of high-efficiency, stable and low-cost industrialization.

[0004] In summary, exploring and developing new electrocatalytic anode materials with higher catalytic activity, stronger durability and cost-effectiveness has become a major issue faced by the scientific research and industrial communities. Such materials not only need to have excellent electrochemical performance to efficiently catalyze key reactions such as OER and MOR, but also need to have good physical and chemical stability to cope with various challenges in long-term operation. SUMMARY

[0005] To solve the above technical problems, the present application provides a preparation method of a quaternary electrocatalytic anode material containing four sub-group metals and its application. The electrocatalytic anode material of the present application uses foamed nickel as a carrier, and a layer of four sub-group metals and their oxides is loaded on the carrier. The material is used as an anode material for anode electrolytic alkaline water oxygen evolution and methanol oxidation reaction, which can significantly reduce the overpotential and improve the stability.

[0006] The specific technical scheme of the present application is as follows:

[0007] In the first aspect, the present application provides a quaternary sub-group metal electrocatalytic anode material, which uses foamed nickel as a carrier, and the surface layer of the foamed nickel is loaded with molybdenum elements, iron elements and another sub-group metal element, and the surface layer is a composite oxide of iron, nickel, molybdenum and another sub-group metal element. Among them, the another sub-group metal element is one of vanadium, tungsten, manganese and cobalt, and the most preferred is vanadium; the molar ratio of nickel element and molybdenum element is 3-8:1; the molar ratio of iron element and another sub-group metal is 0.5-8:1.

[0008] The electrocatalytic anode material of the present application takes the foamed nickel as the carrier, loads the molybdenum metal thereon, and forms a uniform active metal (iron and another metal element of the secondary group) deposition layer on the surface of the carrier through the immersion method. After the material is calcined at high temperature, the metal elements can form stable oxides (quaternary multi-metal oxides) and the close bonding and interaction between the elements, so that the metal d-band center is lowered, and the electronic structure is optimized and reorganized.

[0009] The electrode material composed of the multi-metal oxides can lower the d-band center of the metal through the interaction between the metal and metal and the metal and oxygen element, optimize and reorganize the electronic structure and arrangement of the material, and significantly enhance the covalence of the metal-oxygen (M-O) bond. The enhanced interaction not only stabilizes the structure of the electrocatalytic anode material, but also accelerates the dynamic response of self-reconstruction thereof in the catalytic process, reduces the energy barrier of the reaction, and improves the intrinsic activity and stability.

[0010] Therefore, the material applied as the anode material in the oxygen evolution reaction and the methanol oxidation reaction of the anode electrolytic alkaline water can significantly reduce the overpotential and improve the stability.

[0011] Preferably, the molar ratio of the iron element and the other metal element of the secondary group is 4-8:1.

[0012] The present application finds that the ratio of the other metal element of the secondary group to iron has a crucial influence on the performance of the electrocatalytic electrode anode. Taking the vanadium element as an example, the vanadium element has the multi-electron reaction property and a large number of empty d orbitals, is conducive to the combination with iron, realizes the overall or regional electronic structure regulation, and the electronic interaction between iron and vanadium can change the electronic structure of the catalyst. Therefore, the ratio of iron and vanadium elements can optimize the catalytic performance thereof, and the ratio greater than 6:1 will cause the active sites to be covered and increase the overpotential.

[0013] Preferably, the composite oxide of iron, nickel, molybdenum and the other metal element of the secondary group is formed by the replacement reaction of the foamed nickel loaded with molybdenum with the iron salt and the other metal element of the secondary group salt and then calcined at 200-450℃, more preferably 250-350℃.

[0014] The present application finds that the calcination temperature significantly affects the catalytic performance of the electrocatalytic anode material. When the calcination temperature is low, the metals on the material cannot be closely combined and cannot form firm metal oxides; when the calcination temperature exceeds 300℃, the high temperature damages the carrier and cannot maintain the basic structure, which reduces the electronic transmission efficiency and increases the resistance of the material itself.

[0015] In a second aspect, the present application provides a preparation method of the quaternary electrocatalytic anode material containing four metal elements of the secondary group, which comprises:

[0016] 1) the acid pre-treatment foamed nickel loaded with molybdenum metal is immersed in a soaking solution containing iron salt and another salt of a second group metal element to perform a soaking reaction, and after the reaction, the foamed nickel molybdenum material with iron element and vanadium element deposited on the surface is obtained after drying.

[0017] 2) the foamed nickel molybdenum material with iron element and another second group metal element deposited on the surface is calcined under oxygen at 200-450℃ for 0.5-1.5h to obtain a quaternary metal electrocatalytic anode material.

[0018] The method of the present application uses foamed nickel as a carrier, loads molybdenum metal, and then immerses it in a soaking solution containing iron element and another second group metal element. Through the displacement reaction between elements, the iron element and another second group metal element are deposited on the carrier to form a uniform active metal coating. Through high-temperature calcination, the metal elements form stable oxides and enhance the close bonding and interaction between the elements, thereby moving the metal d-band center down and optimizing and reorganizing the electronic structure.

[0019] Preferably, in step 1), the method of loading molybdenum metal is one of ion exchange, electroplating or high-temperature reduction.

[0020] Preferably, in step 1), the iron salt is one or more of iron sulfate, iron nitrate and iron chloride; and the salt of another second group metal element is one of soluble chloride, nitrate and sulfate of vanadium, tungsten, manganese and cobalt.

[0021] Preferably, in step 1), the content of another second group metal element in the soaking solution is 0.022-0.356mol·L -1 ; more preferably, the content of iron element in the soaking solution is 0.134-0.356mol·L -1 .

[0022] Preferably, in step 1), the soaking reaction time is 10-50 minutes; more preferably, the soaking reaction time is 20-40 minutes.

[0023] Preferably, in step 2), the calcination temperature is 250-350℃.

[0024] In a third aspect, the present application provides the use of the above-mentioned quaternary electrocatalytic anode material containing four second group metal elements in electrocatalytic methanol oxidation reaction.

[0025] The application of the quaternary electrocatalytic anode material of the present application to electrocatalytic methanol oxidation reaction can significantly reduce the overpotential, and the minimum overpotential required is 520mV at a current density of 100mA·cm -2 .

[0026] Preferably, the concentration of methanol in the reaction system is 1-15wt%, more preferably 3-5wt%.

[0027] Preferably, the charge transport medium in the reaction system is potassium hydroxide or sodium hydroxide, and the concentration is 1-50wt%.

[0028] The quaternary electrocatalytic anode material can be applied in commercial electrolytic cells for large-scale electrolysis of methanol oxidation and water splitting for oxygen evolution reaction.

[0029] Preferably, the scale of electrolytic cell used in large-scale application is 1-10m 3 / h, more preferably 1-5m 3 / h.

[0030] Preferably, the working temperature of the commercial electrolytic cell is 40-60℃.

[0031] In the fourth aspect, the application provides application of the above-mentioned quaternary electrocatalytic anode material in alkaline water electrocatalytic oxygen evolution reaction.

[0032] The application of the iron-vanadium-nickel-molybdenum quaternary electrocatalytic anode material in the electrolysis of alkaline water for oxygen evolution can significantly reduce the overpotential. In the process of electrocatalytic alkaline water splitting, a current density of 100mA·cm -2 is achieved, and the minimum required overpotential is 263mV.

[0033] Preferably, the charge transport medium in the reaction system is potassium hydroxide or sodium hydroxide, and the concentration is 1-50wt%.

[0034] The quaternary electrocatalytic anode material can be applied in commercial electrolytic cells for large-scale electrolysis of methanol oxidation and water splitting for oxygen evolution reaction.

[0035] Preferably, the scale of electrolytic cell used in large-scale application is 1-10m 3 / h, more preferably 1-5m 3 / h.

[0036] Preferably, the working temperature of the commercial electrolytic cell is 40-60℃.

[0037] Compared with the prior art, the application has the following beneficial effects:

[0038] (1) The present application is based on four metal elements of iron, nickel, molybdenum and another metal of the secondary group, and constructs an anode electrode material for electrocatalysis mainly composed of quaternary metal and its oxide. The various metal elements significantly enhance the close bonding and interaction force between them by forming a stable oxide structure, which not only promotes the downward shift of the metal d band center, but also optimizes and restructures the electronic arrangement structure. Thus, it exhibits excellent electrocatalytic performance and can be efficiently applied to the anode electrolytic alkaline water oxygen evolution and methanol oxidation reaction. Moreover, the material can be applied to commercial electrolytic cells, opening up new possibilities for improving electrolytic efficiency and energy conversion efficiency.

[0039] (2) The present application provides a simple and efficient method for preparing an electrocatalytic anode material. Through a solution displacement reaction, iron and another metal element of the secondary group are deposited onto a nickel-molybdenum foam carrier, and then high-temperature calcination is performed to form key oxide species and strengthen the connection between the elements.

[0040] (3) The electrocatalytic anode material of quaternary metal oxide prepared by the present application has excellent performance in electrocatalytic water splitting and electrocatalytic methanol oxidation reactions. The presence of multiple metals greatly optimizes and restructures the electronic structure and arrangement of the material, significantly enhances the covalence of the metal-oxygen (M-O) bond, and promotes the dynamic restructuring ability of the catalyst itself. In an alkaline electrolyte, a current density of 100 mA·cm -2 is achieved, and the minimum overpotential required is 263 mV, which is much higher than the current mainstream level. The prepared catalyst also has significant catalytic effect in methanol oxidation reaction, achieving a current density of 100 mA·cm -2 and a minimum overpotential of 520 mV.

[0041] (4) The anode electrocatalyst prepared by the present application can be used in commercial large-scale electrolytic cells for electrocatalytic water splitting and electrocatalytic methanol oxidation reactions, and has stable and efficient catalytic effect. BRIEF DESCRIPTION OF DRAWINGS

[0042] Figure 1 is the SEM image of FVNM;

[0043] Figure 2 is the activity test result of the electrocatalytic oxygen evolution electrode in Test Example 1;

[0044] Figure 3 is the overpotential required by the electrocatalytic oxygen evolution electrode in Test Example 1 at 100 mA·cm -2 ;

[0045] Figure 4 is the activity test result of the electrocatalytic oxygen evolution electrode in Test Example 2;

[0046] Figure 5Activity test results for the electrocatalytic oxygen evolution electrode in Test Example 3;

[0047] Figure 6 Activity test results for the electrocatalytic oxygen evolution electrode in Test Example 4;

[0048] Figure 7 Activity test results for the electrocatalytic oxygen evolution electrode in Test Example 5;

[0049] Figure 8 Activity test results for the electrocatalytic oxygen evolution electrode in Test Example 6;

[0050] Figure 9 Activity test results for the electrocatalytic methanol oxidation electrode in Test Example 7;

[0051] Figure 10 Activity test results for the electrocatalytic oxygen evolution electrode in Test Example 7 at 100 mA·cm -2 The overpotential required below;

[0052] Figure 11 1 m 3 / h commercial electrolysis device used in Test Example 8;

[0053] Figure 12 Activity test results for the electrocatalytic oxygen evolution in Test Example 8;

[0054] Figure 13 Activity test results for the electrocatalytic methanol oxidation in Test Example 8. DETAILED DESCRIPTION

[0055] The application will be further described below in conjunction with examples.

[0056] Example 1

[0057] The preparation process of the FeVNiMo quaternary electrode material is as follows:

[0058] Carrier pretreatment: the nickel foam with a thickness of 1.5 mm, a pore size of 110 ppi, and a size of 1*2 cm was placed in a 1 mol·L -1 -1 dilute hydrochloric acid solution, taken out after ultrasonic cleaning for 30 minutes, and then placed in anhydrous ethanol for ultrasonic cleaning for 30 minutes and dried.

[0059] Molybdenum metal loading: the pretreated nickel foam was placed in a 50 ml, 0.5 mol·L -1 -1 sodium molybdate solution for electroplating, and the current added was 0.5 mA·cm -1 -2, and the electroplating time was 5 minutes. After electroplating, the nickel foam loaded with molybdenum metal (i.e., the nickel foam molybdenum material) was obtained, and the mass ratio of nickel to molybdenum was 9:1.

[0060] Synthesis of FeVNiMo quaternary electrode material: The foam nickel loaded with molybdenum metal was put into 50 ml of soaking solution containing 0.35 g vanadium chloride (0.045 mol·L -1 ) and 5.4 g iron nitrate nonahydrate (0.268 mol·L -1 ). After standing for 30 minutes, it was taken out and put into an oven, dried at 60°C, and then put into a muffle furnace. The temperature was raised to 300°C at a rate of 5°C / min, and then kept for 1 hour. After cooling to room temperature, the FVNM catalytic electrode was obtained. Figure 1 For its SEM image, it can be seen that a layer of deposited and oxidized metal oxide layer is deposited on its surface, making the surface rough, which will be conducive to the electrolysis reaction.

[0061] Examples 2-4

[0062] The preparation method is the same as Example 1, and the only difference is that 0.35 g of vanadium chloride is replaced by different metal salts:

[0063] Example 2: 0.661 g of sodium tungstate (0.045 mol·L -1 ), and the product obtained is denoted as FWNM.

[0064] Example 3: 0.283 g of manganese chloride (0.045 mol·L -1 ), and the product obtained is denoted as FMNM.

[0065] Example 4: 0.292 g of cobalt chloride (0.045 mol·L -1 ), and the product obtained is denoted as FCNM.

[0066] Example 5: ultrapure water, and the product obtained is denoted as NM.

[0067] Example 6

[0068] The preparation method is the same as Example 1, and the only difference is that no electroplating treatment is performed, and the soaking solution is ultrapure water without any metal salt, and the product obtained is denoted as N.

[0069] Example 7

[0070] The preparation method is the same as Example 1, and the only difference is that the foam nickel after pretreatment is soaked in 25 ml of sodium molybdate solution containing 0.05 mol·L -1 for 30 minutes, and then taken out and dried after sufficient replacement. The product obtained is denoted as FUNM-2, and the mass ratio of nickel to molybdenum is 9:1.

[0071] Examples 8-12

[0072] The preparation method is the same as Example 1, and the only difference is that the temperature for calcination and holding in the muffle furnace is:

[0073] Example 8: 200℃.

[0074] Example 9: 250℃.

[0075] Example 10: 350℃.

[0076] Example 11: 400℃.

[0077] Example 12: 450℃.

[0078] Examples 13-17

[0079] The preparation method is the same as that of Example 1, except that the concentration of iron nitrate nonahydrate in the soaking solution is:

[0080] Example 13: 0.022 mol·L -1 .

[0081] Example 14: 0.045 mol·L -1 .

[0082] Example 15: 0.067 mol·L -1 .

[0083] Example 16: 0.134 mol·L -1 .

[0084] Example 17: 0.356 mol·L -1 .

[0085] Examples 18-21

[0086] The preparation method is the same as that of Example 1, except that the soaking time is:

[0087] Example 18: 10 minutes.

[0088] Example 19: 20 minutes.

[0089] Example 20: 40 minutes.

[0090] Example 21: 50 minutes.

[0091] Example 22

[0092] The preparation method is the same as that of Example 1, except that the area of the soaked nickel-molybdenum is replaced by a circle with a diameter of 25 cm, and the soaking solution is soaked in a volume that is proportionally increased, and the concentration of the soaking solution remains unchanged.

[0093] Example 23

[0094] The preparation method is the same as that of Example 1, except that the soaking solution only contains 0.35 g of vanadium chloride (0.045 mol·L-1 ), the product obtained is recorded as VNM.

[0095] Example 24

[0096] The preparation method is the same as that of Example 1, except that only 5.4 g of ferric nitrate nine-water (0.27 mol·L -1 ), the product obtained is recorded as FNM.

[0097] Example 25

[0098] The preparation method is the same as that of Example 1, except that the pretreated and soaked carrier is foamed nickel, and the product obtained is recorded as FVN.

[0099] Performance test

[0100] Test Example 1

[0101] The electrode materials prepared in Examples 1, 23-25 were subjected to linear sweep voltammetry test in 5wt% KOH solution to explore the effect of the quaternary metal-based catalytic electrode on the electrocatalytic water splitting to generate oxygen. The specific test used a saturated Ag / AgCl electrode as a reference electrode, a graphite electrode as a counter electrode, a scan rate of 10 mV / s, and a 5wt% KOH electrolyte. The electrode potential was subjected to iR correction to eliminate the influence caused by solution resistance, etc., and was converted into the electrode potential relative to the reversible electrode (RHE), and the calculation formula was: overpotential (V) = electrode potential + pH*0.0591 + 0.1976-1.23. The results are shown in Figure 2 .

[0102] Figure 3 The overpotential of the four materials when the electrocatalytic water splitting reached a current density of 100 mA·cm -2 From the figure, it can be seen that the quaternary electrode material has the best electrocatalytic water splitting performance, and the overpotential is only 263 mV, while the catalytic performance of the ternary material is also better than that of the binary material. Due to the direct interaction between multiple metals and the interaction between the metals and the connecting oxygen, the isolated metal d band center gradually approaches and fuses with each other, forming a continuous energy band structure, resulting in the downward shift of the d band center. The mutual covalent interaction between the metal and oxygen will cause the transfer, sharing and rearrangement of electrons, thereby enhancing the dynamic response of the self-reconstruction of the catalyst in the catalytic process, which is beneficial to the rapid activation of the OER performance following the lattice oxygen mechanism.

[0103] Test Example 2

[0104] The electrode materials prepared in Examples 1-6 were subjected to linear sweep voltammetry test in 5wt% KOH solution to explore the effect of different metal elements on the performance of the material. The specific test method was the same as that of Test Example 1. The results are shown in Figure 4 .

[0105] Vanadium, tungsten, manganese, cobalt and other elements are used as raw materials, and iron, nickel and molybdenum are added to the prepared materials, which have excellent performance and can significantly reduce the energy consumption of electrolytic water oxygen evolution. Among them, vanadium has the best effect. The possible reason is that the selected elements are transition metal elements in the secondary group, which have a large number of empty orbitals, which is conducive to the mutual combination and bonding of each component, thereby promoting the formation of continuous energy bands, making the electrons transfer, share and rearrange, so that the reactants are more easily adsorbed and dissociated.

[0106] Test Example 3

[0107] The electrode materials prepared in Example 1 and Example 7 were subjected to linear sweep voltammetry test in 5wt% KOH solution to explore the influence of different methods of loading molybdenum on the performance of the material. The specific test method is the same as that in Test Example 1. The results are shown in Figure 5 .

[0108] Different methods of loading molybdenum onto the surface of the foam nickel have no obvious effect on the performance of the material.

[0109] Test Example 4

[0110] The electrode materials prepared in Example 1 and Example 8-12 were subjected to linear sweep voltammetry test in 5wt% KOH solution to explore the influence of calcination temperature on the performance of the material. The specific test method is the same as that in Test Example 1. The results are shown in Figure 6 .

[0111] Calcination temperature significantly affects the catalytic performance of the electrode material. When the calcination temperature is low, the metals on the material cannot be closely combined, and cannot form a firm metal oxide; when the calcination temperature exceeds 300°C, the carrier is damaged by the high temperature, and cannot maintain the basic structure, resulting in a decrease in electron transmission efficiency and an increase in material resistance.

[0112] Test Example 5

[0113] The electrode materials prepared in Example 1 and Example 13-17 were subjected to linear sweep voltammetry test in 5wt% KOH solution to explore the influence of different iron and vanadium ratios on the performance of the material. The specific test method is the same as that in Test Example 1. The results are shown in Figure 7 .

[0114] The ratio of iron and vanadium elements significantly affects the catalytic performance of the electrode material. Vanadium has multi-electron reactivity and a large number of empty d orbitals, which is conducive to the combination with iron to realize the overall or regional electronic structure regulation. The electronic interaction between iron and vanadium can change the electronic structure of the catalyst. Therefore, the ratio of iron and vanadium elements can optimize its catalytic performance, and when the ratio is greater than 6, the active sites will be covered, increasing the overpotential. From Figure 5It can be seen that the preferred iron-vanadium element ratio is 6:1.

[0115] Test Example 6

[0116] The electrode materials prepared in Example 1, Examples 18-21 were subjected to linear sweep voltammetry tests in 5wt% KOH solution to investigate the effect of different soaking times on the performance of the materials. The specific test method is the same as in Test Example 1. The results obtained are shown in Table 6. Figure 8 .

[0117] Different soaking times also have an effect on the electrode materials. It is shown that too long a soaking time will cause excessive iron and vanadium elements to be displaced, covering the active sites on the carrier, resulting in a decrease in catalytic performance.

[0118] Test Example 7

[0119] The electrode materials prepared in Example 1, Examples 22-25 were subjected to linear sweep voltammetry tests in 5wt% KOH, 15wt% methanol solution to investigate the effect of quaternary metal-based catalytic electrodes on the electrocatalytic oxidation of methanol. The specific test method is as follows: a saturated Ag / AgCl electrode was used as the reference electrode, a graphite electrode was used as the counter electrode, the scan rate was 10mV / s, the electrolyte was 5wt% KOH, 15wt% methanol solution. The electrode potential was subjected to iR correction to eliminate the effects caused by solution resistance, etc., and was converted into the electrode potential relative to the reversible electrode (RHE), and the calculation formula was: overpotential (V) = electrode potential + pH*0.0591 + 0.1976-0.85. The results obtained are shown in Table 7. Figure 9 .

[0120] Figure 10 The overpotential of the four materials when the current density of the electrocatalytic water splitting reached 100mA·cm -2 -2 was 530mV, while the catalytic performance of the ternary material was also better than that of the binary material.

[0121] Test Example 8

[0122] Example 19 was placed in a commercial electrolysis device of 1m 3 / h specification for large-scale testing. The electrolysis device is shown in Figure 10 , and is mainly composed of a core electrolysis tank and a supporting gas-liquid separation device. The electrolyte for the electrocatalytic water splitting is 1.0mol·L -1 KOH, and the electrolyte for the electrocatalytic methanol oxidation is 1.0mol·L -1 KOH and 5.0mol·L -1 methanol solution. The working temperature is 60°C. The current density at different voltages is shown in Figure 11 and Figure 12as shown.

Claims

1. A quaternary electrocatalytic anode material, characterized in that: Using nickel foam as a carrier, the surface of the nickel foam is deposited with molybdenum, iron and another transition metal element, and the surface layer is a composite oxide of iron, nickel, molybdenum and another transition metal. The other subgroup metal is one of vanadium, tungsten, manganese, and cobalt; The molar ratio of the iron element to the other subgroup metal element is 0.5-8:1; The composite oxide of iron, nickel, molybdenum and another subgroup metal is formed by first loading molybdenum metal onto nickel foam through ion exchange, electroplating or high-temperature reduction, and then reacting it with iron salt and another subgroup metal before calcining at 200-450 °C.

2. The quaternary electrocatalytic anode material according to claim 1, characterized in that: The molar ratio of nickel to molybdenum is 3-8:1; the molar ratio of iron to another subgroup metal is 4-8:

1.

3. A method for preparing the quaternary electrocatalytic anode material according to claim 1 or 2, characterized in that... include: 1) Load molybdenum metal onto the acid-washed nickel foam to obtain nickel-molybdenum foam material; 2) The foamed nickel-molybdenum material is immersed in an immersion solution containing iron salt and another subgroup metal salt for immersion reaction. After the reaction, it is taken out and dried to obtain foamed nickel-molybdenum material with iron and another subgroup metal deposited on the surface. 3) The foamed nickel-molybdenum material with iron and another subgroup metal deposited on its surface is calcined in an aerobic environment at 200-450 °C for 0.5-3 h to obtain a quaternary electrocatalytic anode material.

4. The preparation method according to claim 3, characterized in that: In step 1): The nickel foam has a thickness of 1-2 mm, a pore size of 80-150 ppi, and an area ranging from 0.0001-10 m². 2 ; The method of loading molybdenum is one of ion exchange, electroplating or high-temperature reduction. In step 2): The iron salt is one or more of ferric sulfate, ferric nitrate and ferric chloride; The other subgroup metal element salt is one of the soluble chloride, nitrate, and sulfate salts of vanadium, tungsten, manganese, and cobalt; The iron content in the soaking solution is 0.022-0.356 mol·L⁻¹. -1 .

5. The preparation method according to claim 3, characterized in that: In step 2), the calcination temperature is 250-350℃.

6. The application of the quaternary electrocatalytic anode material according to claim 1 or 2 or the quaternary electrocatalytic anode material obtained by the preparation method according to any one of claims 3-5 in the electrocatalytic methanol oxidation reaction.

7. The application according to claim 6, characterized in that: The concentration of methanol in the reaction system is 1-10 mol·L⁻¹ -1 ; The charge transport medium in the reaction system is potassium hydroxide or sodium hydroxide, with a concentration of 1-50 wt%. The scale of the electrolytic cells used is 1-10 m. 3 / h.

8. The application of the quaternary electrocatalytic anode material according to claim 1 or 2 or the quaternary electrocatalytic anode material obtained by the preparation method according to any one of claims 3-5 in the alkaline water electrocatalytic oxygen evolution reaction.

9. The application according to claim 8, characterized in that: The charge transport medium in the reaction system is potassium hydroxide or sodium hydroxide, with a concentration of 1-50 wt%. The scale of the electrolytic cells used is 1-10 m. 3 / h.